2002
DOI: 10.1002/14651858.cd003850
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic intravenous antifungal agents to prevent mortality and morbidity in very low birth weight infants

Abstract: We have found some evidence that prophylactic intravenous fluconazole reduces mortality prior to hospital discharge in very low birth weight infants. The meta-analysis suggests that there will be one fewer death in every nine infants treated with this intervention, but the 95% confidence interval around this estimate of effect is wide. The longer term neurodevelopmental consequences for infants exposed to this intervention remain to be determined. It will be important to identify any subgroups of very low birt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
37
0
1

Year Published

2004
2004
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 0 publications
0
37
0
1
Order By: Relevance
“…11 Both studies were designed for partial objectives and leave some questions unanswered. 28,29 Our study focuses on the effects of prophylactic fluconazole on a widespread NICU population over a period of 3 years. This policy proved very effective in all VLBW neonates, not only in ELBW neonates as previously reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Both studies were designed for partial objectives and leave some questions unanswered. 28,29 Our study focuses on the effects of prophylactic fluconazole on a widespread NICU population over a period of 3 years. This policy proved very effective in all VLBW neonates, not only in ELBW neonates as previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…27 The efficacy of fluconazole in reducing both colonization and infection in ELBW neonates has been demonstrated in 1 study. 11,28,29 As in most NICUs, in the late 1990s, our tertiary intensive and subintensive 40-bed unit faced a dramatic increase in frequency and severity of SFI, related to expansion of instrumental activities and procedures and to an increase in the number of preterm births and survival rates of the most immature infants. In light of the protocols that are used for infants with hematologic malignancies and on the strength of our personal observations, in January 2001, we started to give oral or intravenous prophylactic fluconazole to all VLBW neonates, both those with birth weight Ͻ1000 g (ELBW) and those with birth weight 1001 to 1500 g (NE-VLBW).…”
mentioning
confidence: 99%
“…are also concerned about the uncertainty regarding the potential toxicities and emergence of resistant pathogens. 9,15,16 So far, most of the studies on fluconazole prophylaxis in preterm infants were focused on elevation of liver enzymes as a marker for hepatotoxicity. Our data, as well as those of reported studies, show that there was no significant increase in liver enzymes with fluconazole prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…6 Fluconazole prophylaxis has been shown to reduce candida colonization and/or infection in VLBW infants. 4,[7][8][9][10][11] In 2001, Kaufman et al 4 reported results of a small randomized clinical trial showing that the prophylactic intravenous administration of fluconazole prevented fungal colonization and invasive fungal disease in extremely low birth weight (ELBW) infants without adverse effects. In 2005 and 2006, three studies reported data after implementing different fluconazole prophylaxis schedules and showed favorable results.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports suggest a benefit of fluconazole prophylaxis in ELBW infants <1000 g at high risk of fungal infections. 7 But instead of adopting a fluconazole prophylaxis protocol used by others, 9 we followed the recommendation by McGuire et al 17 to select a target population that would benefit most from fluconazole prophylaxis. For infants <26 weeks gestational age and/or <750 g birth weight, we calculated a number needed to treat of 12 to prevent one episode of fungemia and 26 to prevent one death from fungemia.…”
Section: Introductionmentioning
confidence: 99%